'We were shot down!': Earth observing satellites, data surveillance, and NASA's 1982 Global Habitability initiative. (3rd July 2021) - Barton, Jenifer
ABSTRACT: At a United Nations space conference in 1982, NASA officials unveiled Global Habitability, an Earth science initiative to study the physical, chemical, and biological processes of the world's lands, oceans, and atmosphere as a single, integrated system using a fleet of Earth observing satellites. A peaceful and timely initiative that focused on global environmental problems and invited international participation, US officials fully anticipated that it would be favourably received. However, the international response to Global Habitability was not merely unfavourable but openly hostile, leading to the initiative's failure and its almost total obscurity today. This paper explores the history of this unsuccessful initiative to launch a global Earth science research program. Global Habitability was the product of a small group of US scientists who failed to grasp the inherently political nature of data and the importance of the geopolitical context of the 1970s and early 1980s for a scientific and technological research program.